Kimura’s disease Mimicking Hodgkin’s Lymphoma: An unusual cause of parotid swelling - S-A-W Fadilah,; V Shanty,; AS Goh, (Penerbit UKM, 2007)
Kimura’s disease (KD) is a rare, benign chronic inflammatory disease of unknown aetiology, typically presents in the Orientals as subcutaneous masses in the head and neck region that could be easily misdiagnosed as a malignant tumour, leading to unnecessary radical surgery or intensive cytotoxic therapy. It has been mainly reported in the Chinese and Japanese literature. It is difficult to diagnose before tissue biopsy and fine needle aspiration cytology (FNAC) has limited value. Hence, unless the pathologists are aware of this entity, it might be mistaken as a malignant lesion. We encountered a case of KD in a Malay patient presenting as a parotid mass that was initially diagnosed as Hodgkin’s lymphoma (HL). This disorder should be suspected in young male Asian patients presenting with a painless unilateral mass in the head and neck region with associated hypereosinophilia